NTRK2-related developmental and epileptic encephalopathy: Report of 5 new cases. (November 2021) - Yoganathan, Sangeetha; Arunachal, Gautham; Gowda, Vykuntaraju K; Vinayan, Kollencheri Puthenveettil; Thomas, Maya; Whitney, Robyn; Jain, Puneet
Abstract: Purpose: This study aimed to describe the phenotype of five new cases of NTRK2 -related developmental and epileptic encephalopathy (DEE). Methods: The clinical features, EEG, neuroimaging and genetics were reviewed for cases with likely pathogenic and pathogenic NTRK2 variants and then summarized. Results: Five cases of NTRK2 -related DEE were identified. Four had a previously described recurrent variant in NTRK2 and one had a novel variant. The phenotype was characterized by early- onset seizures (infantile spasms, later evolving to multifocal seizures), global developmental delay, variable movement disorders, microcephaly and optic nerve hypoplasia. Conclusions: This series further expands our knowledge of the phenotype and genotype of NTRK2 -related DEE. Highlights: NTRK2-related DEE often presents with early onset seizures, frequently infantile spasms. Seizures are usually drug-refractory. Optic nerve hypoplasia and movement disorders are common.